2016
DOI: 10.1590/s0104-129020162621
|View full text |Cite
|
Sign up to set email alerts
|

Near miss e mulheres negras

Abstract: ResumoIntrodução: A mortalidade materna apresenta grande diferença entre os países desenvolvidos e em desenvolvimento e espelha a qualidade da assistência prestada à saúde da mulher. Para evidenciar melhor essa assistência, novos métodos de estudo vêm sendo utilizados, entre eles a investigação das morbidades maternas graves -near misses. Objetivo: Analisar os fatores de risco para ocorrência de near miss nas diferentes raças/cores das mulheres residentes em três municípios da Região Metropolitana de Curitiba.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
(7 reference statements)
1
5
0
7
Order By: Relevance
“…A previous report on data from Brazil showed that women with underlying disorders had a higher risk of near miss events and nonwhites had more chronic diseases than whites [5]. In our study, the nonwhite group who developed SMO had a lower prevalence of HIV/AIDS and chronic hypertension.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…A previous report on data from Brazil showed that women with underlying disorders had a higher risk of near miss events and nonwhites had more chronic diseases than whites [5]. In our study, the nonwhite group who developed SMO had a lower prevalence of HIV/AIDS and chronic hypertension.…”
Section: Discussionsupporting
confidence: 47%
“…Underlying social-demographic conditions and previous clinical comorbidities are likely to influence maternal and perinatal outcomes [5, 8]. Low level of school education is considered a risk factor for SMO [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations